Treatment and outcomes of arthrogryposis in the upper extremity. Issue 3 (3rd July 2019) - Oishi, Scott; Agranovich, Olga; Zlotolow, Dan; Wall, Lindley; Stutz, Chris; Pajardi, Giorgio; Novelli, Chiara; Abdel Ghani, Hisham; Jester, Andrea; Vuillermin, Carley; James, Michelle; Manske, Mary C.; et al.
Abstract: Upper extremity involvement in patients with arthrogryposis multiplex congentia is quite frequent. Treatment initially consists of stretching and splinting as significant gains can be seen in the first years of life. The goal of any surgical procedure is to improve upper extremity function and performance of daily living activities, yet it is important to treat each patient individually and understand that areas do not always need to be addressed surgically. Despite overall lower functioning scores in this patient population, quality of life scores are comparable to the general aged adjusted population. This article will discuss the clinical presentation, treatment procedures and outcomes when addressing the upper extremities of patients presenting with arthrogryposis.